Poor Safety and Tolerability Hamper Reaching a Potentially Therapeutic Dose in the Use of Thalidomide for Alzheimer’s Disease: Results from a Double-Blind, Placebo-Controlled Trial - Decourt, Boris; Drumm-Gurnee, Denise; Wilson, Jeffrey; Jacobson, Sandra; Belden, Christine; Sirrel, Sherye; Ahmadi, Michael; Shill, Holly; Powell, Jessica; Walker, Aaron; Gonzales, Amanda; Macias, Mimi; et al. (Current Alzheimer Research, 2017)
Introduction: To date there is no cure for Alzheimer’s disease (AD). After amyloid beta immunotherapies have failed to meet primary endpoints of slowing cognitive decline in AD subjects, the inhibition of the beta-secretase BACE1 appears as a promising therapeutic approach. Pre-clinical data obtained in APP23 mice suggested that the anti-cancer drug thalidomide decreases brainBACE1 and Aβ levels. This prompted us to develop an NIH-supported Phase IIa clinical trial to test the potential of thalidomide for AD. We hypothesized that thalidomide can decrease or stabilize brain amyloid deposits, which would result in slower cognitive decline in drug- versus placebo-treated subjects. Methods: This was a 24-week, randomized, double-blind, placebo-controlled, parallel group study with escalating dose regimen of thalidomide with a target dose of 400mg daily in patients with mild to moderate AD. The primary outcome measures were tolerability and cognitive performance assessed by a battery of tests. Results: A total of 185 subjects have been pre-screened, out of which25 were randomized. Mean age of the sample at baseline was 73.64 (±7.20) years; mean education was 14.24 (±2.3) years; mean MMSE score was 21.00 (±5.32); and mean GDS score was 2.76 (±2.28).Among the 25 participants, 14 (56%) terminated early due to adverse events, dramatically decreasing the power of the study. In addition, those who completed the study (44%) never reached the estimated therapeutic dose of 400 mg/day thalidomide because of reported adverse events. The cognitive data showed no difference between the treated and placebo groups at the end of the trial. Conclusion: This study demonstrates AD patients have poor tolerability for thalidomide, and are unable to reach a therapeutic dose felt to be sufficient to have effects on BACE1. Because of poor tolerability, this study failed to demonstrate a beneficial effect on cognition.
Keywords: Adverse events